Development of Wooden Charcoal for Toluene Adsorption - สุยะพันธ์, องอาจ; ไชยศรีหา, กมลขวัญ; ทองอินทร์, นิศารัตน์; ศรีชาดา, อัครเดช; มุสิกพงศ์, พิรัชฎา; มีวาสนา, ขนิษฐา (KKU Science Journal, 2015)
Our experimental research emphasized on the development of the rubber-based charcoal adsorbent. Two types of wooden charcoal were prepared from Tamarind Tree (Tamarindus indica) and Semal tree (Bombax ceiba L.). The adsorption experiments were conducted in the test chamber. The toluene concentration in the chamber was analyzed every 5 minutes using gas chromatography. The maximum adsorption capacities found within experimental time (50 minutes) were 393.05 and 379.24 mg/g for Tamarind tree and Semal tree, respectively. Because of its higher adsorption capacity, Tamarind tree charcoal power was chosen to further develop as an adsorbent. The adsorbent sheet was developed by mixing Tamarind tree charcoal with rubber. Then the mixing was press to make adsorbent sheet. The adsorption capacity of the adsorbent sheet was also studied. However, the toluene adsorption capacity of the developed adsorbent sheets (202.96 mg/g) was found to be lower than that of charcoal adsorbents. The decrease of surface area was the main reason of this finding.